2020
DOI: 10.3389/fphys.2020.603193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-Term Kinesiology Taping on Knee Proprioception and Quadriceps Performance in Healthy Individuals

Abstract: Background : Kinesiology taping (KT) is well known measure for preventing musculoskeletal injuries. Our study aims to explore the actual effects of KT on healthy participants’ knee proprioception and quadriceps performance within 1 h. Methods : A total of 35 healthy male amateur runners were recruited in our study. Four taping sequences were randomly allocated to four different weeks, namely, no taping, placebo taping, KT with tension, and KT with no tension. A CON-TREX isoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
(63 reference statements)
0
13
0
1
Order By: Relevance
“…All tapes were accomplished by a single experienced physical therapist who was not involved in the recruitment and assessment. The FKT and ABT consistency with 50% tension was maintained using the following equation ( Wei et al, 2020 ), and the ST was applied without tension. where x is the actual length measured from the origin and insertion and the anchor length of the KT was set to 4 cm (2 cm each for the proximal and distal sites).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All tapes were accomplished by a single experienced physical therapist who was not involved in the recruitment and assessment. The FKT and ABT consistency with 50% tension was maintained using the following equation ( Wei et al, 2020 ), and the ST was applied without tension. where x is the actual length measured from the origin and insertion and the anchor length of the KT was set to 4 cm (2 cm each for the proximal and distal sites).…”
Section: Methodsmentioning
confidence: 99%
“…All tapes were accomplished by a single experienced physical therapist who was not involved in the recruitment and assessment. The FKT and ABT consistency with 50% tension was maintained using the following equation (Wei et al, 2020), and the ST was applied without tension.…”
Section: Taping Methodsmentioning
confidence: 99%
“…In isokinetic muscle strength tests, several velocities, including 60 or 90°/s for maximal contraction test and 120 or 180°/s for muscle endurance test were selected in accordance with a previous experiment from our laboratory and previous studies. 19 , 31 , 32 However, previous studies showed that slower isokinetic angular velocities mechanically overload the knee, irritating the joint and exacerbating symptoms. Consequently, we used 90 and 180°/s velocities in this study, which were also commonly used for elderly and KOA.…”
Section: Methodsmentioning
confidence: 99%
“…Though regular treatment options like stretching of lower extremity muscles and application of ice is found to be beneficial for reducing the symptoms and swelling of PFPS, Kinesio taping is found beneficial for the subjects with PFPS (Wei et al, 2020). In recent times, along with Taping, several strengthening exercises and stretching programs were also prescribed to patients with different syndromes to get a better output (Gohil et al, 2021).…”
Section: The Mechanical Correction Technique As In Kinesio Tapingmentioning
confidence: 99%